Biodegradable zinc-germanium alloy material and preparation method thereof

By adding trace germanium elements to pure zinc and smelting and heat treatment, zinc-germanium alloy materials with high mechanical properties and suitable degradation rates are prepared, which solves the problem of insufficient degradation speed of existing zinc alloy materials and has broad medical application potential.

CN119800155APending Publication Date: 2025-04-11CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411904911.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

There are shortcomings in the degradation rate of existing zinc alloy materials. Some materials degrade too fast, while others degrade too slowly, making it difficult to meet the application needs in the medical field.

Method used

By adding trace amounts of germanium to pure zinc, smelting and heat treatment, zinc-germanium alloy materials with high mechanical properties, good biocompatibility and degradability were prepared.

Benefits of technology

This zinc-germanium alloy material has high mechanical properties and suitable degradation rate. It is suitable for designing new bone implant materials and cardiac stents, and has a wide range of application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800155A_ABST
    Figure CN119800155A_ABST
Patent Text Reader

Abstract

The invention relates to the field of metal materials, in particular to a biodegradable zinc-germanium alloy material and a preparation method thereof. According to the technical scheme, the Ge-Zn-Zn alloy comprises the following metals in percentage by mass: 1.5-4.5% of Ge and the balance of Zn, or comprises the following metals in percentage by mass: 1.5-4.5% of Ge, 0.2-0.8% of silver and the balance of Zn. The biodegradable zinc-germanium alloy material has the beneficial effects that a trace amount of germanium element is added into pure zinc, and the biodegradable zinc-germanium alloy material with relatively high mechanical property, good biocompatibility and degradability is obtained through smelting and heat treatment; besides, a trace amount of silver element can be added as required, so that the zinc-germanium alloy has higher mechanical property, proper degradation rate and better antibacterial property, has huge potential of being applied to design of novel bone implant materials and heart stents, and has wide application prospects in biodegradable materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal materials, and in particular to a biodegradable zinc-germanium alloy material and a preparation method thereof. Background Art

[0002] For magnesium-based alloys and iron-based alloys, most magnesium-based alloys have the disadvantages of too fast degradation and iron-based alloys have the disadvantages of too slow degradation. The corrosion rate of zinc and its alloys is between the two, and they are considered to be more likely to be used in biodegradable metal materials for human implants. At the same time, Zn is a metal trace element that is essential to the human body and second only to Fe in content, and plays an important role in human physiological activities. At present, zinc alloy degradable biomaterials mainly improve the mechanical properties of zinc alloys by adding alloying elements and through deformation and other means. Compared with polymer materials, ceramic materials and the other two degradable metal materials, zinc alloys have gradually become a new type of medical degradable metal material due to their excellent biocompatibility and more suitable degradation rate than magnesium alloys and iron-based alloys. It is the current development direction of new medical metal materials at home and abroad. At the same time, it is also urgent for scientific researchers to further study and develop biodegradable zinc alloys with suitable corrosion resistance and better comprehensive mechanical properties, so as to use them in clinical applications as soon as possible.

[0003] Although nearly ten types of zinc alloy biodegradable alloy systems have been developed, with the increasing demand for biodegradable alloy materials, more zinc alloy systems are still needed to be developed as potential materials for implants. Therefore, developing a new type of biodegradable zinc alloy has broad development prospects and far-reaching significance for broadening the application of zinc alloys in the field of biodegradable medical materials. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned defects in the prior art and provide a biodegradable zinc-germanium alloy material and a preparation method thereof. By adding a trace amount of germanium element to pure zinc, and undergoing smelting and heat treatment, a biodegradable zinc-germanium alloy material with high mechanical properties, good biocompatibility and degradability is obtained; in addition, the zinc-germanium alloy has high mechanical properties and a suitable degradation rate, has great potential for application in the design of new bone implant materials and heart stents, and has broad application prospects in biodegradable materials.

[0005] The present invention provides a biodegradable zinc-germanium alloy material, and its technical solution is: calculated by mass percentage, it comprises the following metals: Ge 1.5-4.5%, and the balance is Zn.

[0006] Preferably, the biodegradable zinc-germanium alloy material mentioned in the present invention comprises the following metals by mass percentage: 1.5% Ge and the balance Zn.

[0007] Preferably, the biodegradable zinc-germanium alloy material mentioned in the present invention comprises the following metals by mass percentage: Ge 2.5% and the balance Zn.

[0008] Preferably, the biodegradable zinc-germanium alloy material mentioned in the present invention comprises the following metals by mass percentage: 3.5% Ge and the balance Zn.

[0009] Preferably, the biodegradable zinc-germanium alloy material mentioned in the present invention comprises the following metals by mass percentage: 4.5% Ge and the balance Zn.

[0010] Preferably, the method for preparing the biodegradable medical alloy mentioned in the present invention comprises the following steps: 1. According to the above ratio of zinc and germanium, in an argon protective atmosphere, after melting the metal zinc at a temperature of 550°C to 650°C, adding a Ge source, and continuing to heat the Ge source at 550°C to 650°C until the metal germanium is melted, and then pouring the molten metal into a preheated cast steel mold, and when the surface temperature of the metal mold drops to 100°C, taking out the casting to obtain a blocky zinc-germanium alloy ingot; 2. After the zinc-germanium alloy ingot is cut, it is placed in a homogenizing heat treatment furnace for homogenizing treatment to obtain a biodegradable medical alloy.

[0011] Preferably, the molten metal is poured into a steel casting mold preheated to 200°C.

[0012] Preferably, the homogenization heat treatment is carried out at 250° C. for 12 h under the protection of ferrous sulfide.

[0013] Another biodegradable medical alloy mentioned in the present invention comprises the following metals by mass percentage: Ge 1.5-4.5%, silver 0.2-0.8%, and the balance Zn.

[0014] The method for preparing the biodegradable medical alloy mentioned in the present invention comprises the following steps: 1. According to the ratio of zinc, germanium and silver, in an argon protective atmosphere, after melting the metal zinc at a temperature of 550°C to 650°C, add the Ge source, continue to heat the Ge source at 550°C to 650°C until the metal germanium melts, raise the temperature to 650°C to 700°C, add the Ag source until it is completely melted, and stir to fully mix the metal liquid; then, cast the molten metal liquid into a cast steel mold preheated to 200°C, wait until the surface temperature of the metal mold drops to 100°C, take out the casting to obtain a blocky zinc-germanium-silver alloy ingot; 2. After the zinc-germanium-silver alloy ingot is cut, it is placed in a homogenization heat treatment furnace and subjected to homogenization heat treatment at 250°C for 12 h under the protection of ferrous sulfide to obtain a biodegradable medical alloy.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The present invention improves the mechanical properties of pure Zn by adding trace elements Ge of different mass fractions to pure Zn, so that fatigue resistance is better; Ge is an effective grain refiner of Zn, which can refine grains during plastic deformation and improve the mechanical properties of zinc alloys; at the same time, Ge normalizes many physiological functions of the human body and can be used to design implant materials for orthopedic applications; Second, the present invention can improve the mechanical properties of pure Zn by adding trace elements Ge and trace elements AG of different mass fractions to pure Zn, so that fatigue resistance is better; the mechanical properties of zinc alloy are also improved, and the zinc-germanium-silver alloy can better improve the antibacterial property; The above two alloys have high mechanical properties and suitable degradation rates, and have great potential for application in the design of new bone implant materials and heart stents, and have broad application prospects in biodegradable materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the X-ray diffraction pattern of the biodegradable alloy material obtained in Examples 1-5; Figure 2 is a metallographic picture of the biodegradable alloy material obtained in Example 1; Figure 3 is a metallographic picture of the biodegradable alloy material obtained in Example 2; Figure 4 is a metallographic picture of the biodegradable alloy material obtained in Example 3; Figure 5 is a metallographic picture of the biodegradable alloy material obtained in Example 4; Figure 6 is a metallographic picture of the biodegradable alloy material obtained in Example 5; Figure 7 This is a metallographic picture of pure Zn metal material; Figure 8 is the potentiodynamic polarization curve of the biodegradable alloy material obtained in Examples 1-5; Fig. 9 This is the inhibition zone diagram of pure Zn metal material against Escherichia coli; Fig.10 This is the antibacterial zone diagram of the biodegradable alloy material obtained in Example 1 against Escherichia coli; Fig.11 This is the antibacterial zone diagram of the biodegradable alloy material obtained in Example 2 against Escherichia coli; Fig.12 This is the antibacterial zone diagram of the biodegradable alloy material obtained in Example 3 against Escherichia coli; Fig.13is the antibacterial zone diagram of the biodegradable alloy material obtained in Example 4 against Escherichia coli; Fig.14 This is the antibacterial zone diagram of the biodegradable alloy material obtained in Example 5 against Escherichia coli; Fig.15 It is the hemolysis rate of the biodegradable alloy material leaching solution obtained in Examples 1-5. DETAILED DESCRIPTION

[0017] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. Example 1

[0018] The biodegradable medical alloy mentioned in the present invention comprises the following metals by mass percentage: 1.5% Ge, the balance being Zn and inevitable impurities; The preparation method of the biodegradable medical alloy mentioned in the present invention comprises the following specific steps: (1) Zinc-germanium alloy smelting: Pure Zn and pure Ge are used as raw materials, and the smelting equipment uses a graphite crucible to melt the alloy. 1614.21 g of charge Zn is placed in a graphite crucible and heated to 550 ℃~650 ℃ in a pit furnace. After the Zn source is completely melted, 24.58 g of charge Ge is added, and the Ge source is continued to be heated at 550 ℃~650 ℃. After the Ge source is completely melted, stir to fully mix the molten metal. After keeping warm for 20 minutes, the molten metal is poured into a cast steel mold that has been preheated to 200 ℃. The molten metal must not be interrupted during the pouring process to prevent defects in the casting. When the surface temperature of the metal mold drops to 100 ℃, take out the casting to obtain a blocky zinc-germanium alloy ingot; (2) Homogenization heat treatment: After the zinc-germanium alloy ingot is cut, it is placed in a homogenization heat treatment furnace and subjected to homogenization heat treatment at 250 °C for 12 h under the protection of ferrous sulfide. Example 2

[0019] The present invention provides a biodegradable medical alloy, which comprises the following metals by mass percentage: 2.5% Ge, the balance being Zn and unavoidable impurities; The specific steps of its preparation method are as follows: (1) Smelting of zinc-germanium alloy: Pure Zn and pure Ge are used as raw materials, and the smelting equipment uses a graphite crucible to melt the alloy. 1614.2 g of charge Zn is placed in a graphite crucible and heated to 550 ℃~650 ℃ in a pit furnace. After the Zn source is completely melted, 41.39 g of charge Ge is added, and the Ge source is continued to be heated at 550 ℃~650 ℃. After the Ge source is completely melted, stir to fully mix the molten metal. After keeping warm for 20 minutes, the molten metal is poured into a cast steel mold that has been preheated to 200 ℃. The molten metal must not be interrupted during the pouring process to prevent defects in the casting. When the surface temperature of the metal mold drops to 100 ℃, take out the casting to obtain a blocky zinc-germanium alloy ingot.

[0020] (2) Homogenization heat treatment: After the zinc-germanium alloy ingot is cut, it is placed in a homogenization heat treatment furnace and subjected to homogenization heat treatment at 250 °C for 12 h under the protection of ferrous sulfide. Example 3

[0021] The biodegradable medical alloy mentioned in the present invention comprises the following metals by mass percentage: 1.5% Ge, the balance being Zn and inevitable impurities; The specific steps of its preparation method are as follows: (1) Smelting of zinc-germanium alloy: Pure Zn and pure Ge are used as raw materials, and the smelting equipment uses a graphite crucible to melt the alloy. 1614.21 g of charge Zn is placed in a graphite crucible and heated to 550 ℃~650 ℃ in a pit furnace. After the Zn source is completely melted, 58.55 g of charge Ge is added, and the Ge source is continued to be heated at 550 ℃~650 ℃. After the Ge source is completely melted, stir to fully mix the molten metal. After keeping warm for 20 minutes, the molten metal is poured into a cast steel mold that has been preheated to 200 ℃. The molten metal must not be interrupted during the pouring process to prevent defects in the casting. When the surface temperature of the metal mold drops to 100 ℃, take out the casting to obtain a blocky zinc-germanium alloy ingot.

[0022] (2) Homogenization heat treatment: After the zinc-germanium alloy ingot is cut, it is placed in a homogenization heat treatment furnace and subjected to homogenization heat treatment at 250 °C for 12 h under the protection of ferrous sulfide. Example 4

[0023] The biodegradable medical alloy mentioned in the present invention comprises the following metals by mass percentage: 1.5% Ge, the balance being Zn and inevitable impurities; The specific steps of its preparation method are as follows: (1) Smelting of zinc-germanium alloy: Pure Zn and pure Ge are used as raw materials, and the smelting equipment uses a graphite crucible to melt the alloy. 1614.21 g of charge Zn is placed in a graphite crucible and heated to 550 ℃~650 ℃ in a pit furnace. After the Zn source is completely melted, 76.06 g of charge Ge is added, and the Ge source is continued to be heated at 550 ℃~650 ℃. After the Ge source is completely melted, stir to fully mix the molten metal. After keeping warm for 20 minutes, the molten metal is poured into a cast steel mold that has been preheated to 200 ℃. The molten metal must not be interrupted during the pouring process to prevent defects in the casting. When the surface temperature of the metal mold drops to 100 ℃, take out the casting to obtain a blocky zinc-germanium alloy ingot.

[0024] (2) Homogenization heat treatment: After the zinc-germanium alloy ingot is cut, it is placed in a homogenization heat treatment furnace and subjected to homogenization heat treatment at 250°C for 12 h under the protection of ferrous sulfide. Example 5

[0025] The biodegradable medical alloy mentioned in the present invention comprises the following metals by mass percentage: Ge 4.5%, AG 0.2%, and the balance Zn and unavoidable impurities; The specific steps of its preparation method are as follows: (1) Smelting of zinc-germanium-silver alloy: Pure Zn, pure Ge and high-purity flake silver powder are used as raw materials, and the smelting equipment uses a graphite crucible to melt the alloy. 1614.21 g of charge Zn is placed in a graphite crucible and heated to 550℃~650℃ in a pit furnace. After the Zn source is completely melted, 76.22 g of charge Ge is added, and the Ge source is continued to be heated at 550℃~650℃. After the Ge source is completely melted, the temperature is raised to 650℃~700℃ and the Ag source is added until it is completely melted. Stir to fully mix the molten metal. After keeping warm for 20 minutes, the molten metal is poured into a cast steel mold that has been preheated to 200℃. The molten metal must not be interrupted during the pouring process to prevent defects in the casting. When the surface temperature of the metal mold drops to 100℃, the casting is taken out to obtain a blocky zinc-germanium-silver alloy ingot.

[0026] (2) Homogenization heat treatment: After the zinc-germanium-silver alloy ingot is cut, it is placed in a homogenization heat treatment furnace and subjected to homogenization heat treatment at 250°C for 12 h under the protection of ferrous sulfide.

[0027] Experimental example: Figure 1 The following are X-ray diffraction patterns of pure zinc and Zn-Ge alloy. The experiment found that the diffraction peak intensity of α-Zn is relatively large, and only α-Zn phase is detected in the spectrum of pure Zn. In addition to α-Zn phase, eutectic Ge phase is also detected in Zn-Ge alloy. As the amount of Ge added increases, the diffraction peak intensity of the eutectic Ge phase also increases.

[0028] like Figure 2-6 As shown in the metallographic (50×) image, regular polygonal α-Zn phases were observed on the pure zinc sample. In the Zn-1.5Ge alloy, the gray eutectic Ge phase was distributed along the grain boundaries of the α-Zn phase. With the continuous increase of Ge element, coarse eutectic Ge phase and continuously refined α-Zn phase gradually formed in the cast sample.

[0029] A three-electrode electrochemical workstation was used to perform potentiodynamic polarization tests in SBF simulated body fluid. During the electrochemical test, Zn alloy was used as the working electrode, platinum electrode was used as the auxiliary electrode, and saturated calomel electrode (SCE) was used as the reference electrode. The polarization test was performed at a scan rate of 1 mV / s at 37 °C, and the scanning potential range was -500 mV to 1000 mV. An immersion experiment was performed in a constant temperature water bath at 37 °C to determine the degradation rate of the alloy in SBF simulated body fluid. At least five measurements were performed for each sample group to obtain the potentiodynamic polarization curve as shown in the figure. Figure 7 The corrosion parameters of the cathode and anode parts of the polarization curves were analyzed by linear fitting and Tafel extrapolation, including corrosion rate, corrosion potential (E corr ) and corrosion current density (I corr ), the Tafel fitting parameters of the potentiodynamic polarization curves of the biodegradable alloy materials obtained in Examples 1-5 and pure zinc are shown in Table 1.

[0030] Table 1

[0031] Table 1 E corr Represents the corrosion potential, I corr Represents corrosion current, and Corrision rate represents corrosion speed. As shown in Table 1, adding Ge material to pure Zn can improve the corrosion resistance of alloy materials. Figure 7 From the potentiodynamic polarization diagram, with the addition of Ge element, the corrosion potential (E corr ) gradually moves positively, and the corrosion current density (I corr ) and corrosion rate (V corr ) shows a trend of first increasing and then decreasing. The as-cast Zn-4.5Ge alloy has lower corrosion current density and corrosion rate than pure Zn and other Zn-xGe alloys, which indicates that the Zn-4.5Ge alloy has the best corrosion resistance.

[0032] The biodegradable alloy materials obtained in Examples 1-5 were subjected to an antibacterial test on Escherichia coli to compare the antibacterial effects of Escherichia coli at different Ge contents. The larger the inhibition zone, the better the antibacterial performance. Figure 8-12As shown, both the Zn metal material and the degradable zinc-germanium alloy material obtained by the present invention have antibacterial zones, among which the antibacterial zone of the degradable zinc-germanium alloy material obtained by the present invention has the largest range and is clearer.

[0033] The hemolysis rate of the biodegradable alloy material leaching solution obtained in Examples 1-5 was tested. Fig.15 It can be seen that the hemolysis rates of pure Zn and Zn-xGe are both lower than the safety threshold (5%), which indicates that the alloys studied have good blood compatibility. In addition, except for the hemolysis rate of Zn-3.5Ge (1.097%) which is slightly higher than that of pure Zn (0.889%), the hemolysis rates of other alloys are lower than that of pure Zn. Moreover, the hemolysis rate of Zn-4.5Ge is the lowest, at 0.528%, which indicates that Zn-4.5Ge has the best blood compatibility.

[0034] It can be seen that the degradable alloy described in the present invention has good mechanical properties, good antibacterial properties and a suitable degradation rate, has great potential for application in the design of orthopedic implant materials, and has broad application prospects in biodegradable materials.

[0035] The above are only some preferred embodiments of the present invention. Any person skilled in the art may modify the above technical solutions or modify them into equivalent technical solutions. Therefore, the corresponding simple modifications or equivalent transformations made according to the technical solutions of the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A biodegradable zinc-germanium alloy material, characterized by: Calculated by mass percentage, the following metals are included: Ge 1.5~4.5%, and the balance is Zn.

2. The biodegradable medical alloy according to claim 1, characterized in that: The following metals are included by mass percentage: Ge 1.5%, and the balance is Zn.

3. The biodegradable medical alloy according to claim 1, characterized in that: The following metals are included by mass percentage: Ge 2.5%, and the balance is Zn.

4. The biodegradable medical alloy according to claim 1, characterized in that: The following metals are included by mass percentage: Ge 3.5%, and the balance is Zn.

5. The biodegradable medical alloy according to claim 1, characterized in that: The following metals are included by mass percentage: Ge 4.5%, and the balance is Zn.

6. The method for preparing the biodegradable medical alloy according to any one of claims 1 to 5, characterized in that: The following steps are involved:

1. According to the above ratio of zinc and germanium, in an argon protective atmosphere, after melting the metal zinc at a temperature of 550°C to 650°C, adding a Ge source, and continuing to heat the Ge source at 550°C to 650°C until the metal germanium is melted, and then pouring the molten metal into a preheated cast steel mold, and when the surface temperature of the metal mold drops to 100°C, taking out the casting to obtain a blocky zinc-germanium alloy ingot; 2. After the zinc-germanium alloy ingot is cut, it is placed in a homogenizing heat treatment furnace for homogenizing treatment to obtain a biodegradable medical alloy.

7. The method for preparing the biodegradable medical alloy according to claim 6, characterized in that: The molten metal is poured into a steel casting mold preheated to 200°C.

8. The method for preparing the biodegradable medical alloy according to claim 7, characterized in that: Homogenization heat treatment was carried out at 250℃ for 12 h under the protection of ferrous sulfide.

9. A biodegradable medical alloy, characterized by: Calculated by mass percentage, the following metals are included: Ge 1.5-4.5%, silver 0.2-0.8%, and the balance is Zn.

10. The method for preparing the biodegradable medical alloy according to claim 9, characterized in that The following steps are involved:

1. According to the ratio of zinc, germanium and silver, in an argon protective atmosphere, after melting the metal zinc at a temperature of 550°C to 650°C, add the Ge source, continue to heat the Ge source at 550°C to 650°C until the metal germanium melts, raise the temperature to 650°C to 700°C, add the Ag source until it is completely melted, and stir to fully mix the metal liquid; then, cast the molten metal liquid into a cast steel mold preheated to 200°C, wait until the surface temperature of the metal mold drops to 100°C, take out the casting to obtain a blocky zinc-germanium-silver alloy ingot; 2. After the zinc-germanium-silver alloy ingot is cut, it is placed in a homogenizing heat treatment furnace and subjected to homogenizing heat treatment at 250°C for 12 hours under the protection of ferrous sulfide to obtain a biodegradable medical alloy.

Citation Information

Cited By

  • A biodegradable zinc-germanium-silver-selenium alloy material and a preparation method thereof

    CN122669265A